2014
DOI: 10.3109/10715762.2014.927578
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the expression and inflammatory activity of NADPH oxidase after spinal cord injury

Abstract: Reactive oxygen species and the NADPH oxidase (NOX) enzyme are both up-regulated after spinal cord injury (SCI) and play significant roles in promoting post-injury inflammation. However, the cellular and temporal expression profile of NOX isotypes, including NOX2, 3 and 4, after SCI is currently unclear. The purpose of this study was to resolve this expression profile and examine the effect of inhibition of NOX on inflammation after SCI. Briefly, adult male rats were subjected to moderate contusion SCI. Double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 36 publications
1
70
0
Order By: Relevance
“…Through co-labeling of ox-DHE and gp91 phox we observed a significant increase in NOX2 activation in macrophage/microglia at the lesion epicenter of 14 MO vs. 4 MO SCI mice. Low levels of gp91 phox expression have also been shown in neurons and astrocytes following traumatic brain injury (TBI) and SCI (Cooney et al, 2014; Dohi et al, 2010), and we confirmed expression of gp91 phox in these cells is unaffected by age. We also observed that other unidentified cells also account for ~20% ROS production at 7 dpi.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Through co-labeling of ox-DHE and gp91 phox we observed a significant increase in NOX2 activation in macrophage/microglia at the lesion epicenter of 14 MO vs. 4 MO SCI mice. Low levels of gp91 phox expression have also been shown in neurons and astrocytes following traumatic brain injury (TBI) and SCI (Cooney et al, 2014; Dohi et al, 2010), and we confirmed expression of gp91 phox in these cells is unaffected by age. We also observed that other unidentified cells also account for ~20% ROS production at 7 dpi.…”
Section: Discussionsupporting
confidence: 82%
“…Although there was no significant difference in NOX2 gene expression or protein level due to age (Supplementary Fig. 3A&D-D’), NOX2 is the main superoxide-generating enzyme found in macrophages and has been detected in microglia/macrophages following rat contusion SCI (Cooney et al, 2014). To further investigate whether age alters macrophage-specific NOX2 expression and ROS production, we then performed triple-labeling with TomL, DHE, and the anti-gp91 phox antibody, which identifies the membrane component of NOX2 in cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the central nervous system consists largely of lipids, neuronal tissues such as the spinal cord are highly vulnerable to oxidative injury. Oxidative stress leads to oxidation of polyunsaturated fatty acids and proteins in the neurons, damages the DNA helix, and causes cell death and consumption of antioxidant enzymes that are capable of scavenging reactive oxygen species [54]. Due to elevated oxidative stress in the spinal cord, SOD levels were shown to decrease [23].…”
Section: Discussionmentioning
confidence: 98%